2004
DOI: 10.1002/ajmg.a.30029
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐bp deletion mutation of PTPN11 in an infant with severe Noonan syndrome including hydrops fetalis and juvenile myelomonocytic leukemia

Abstract: A de novo 3-bp deletion (179-181delGTG) was identified at exon 3 of the PTPN11 gene in a female infant with severe Noonan phenotype including hydrops fetalis and juvenile myelomonocytic leukemia. Since the 3-bp deletion is predicted to result in loss of the 60th glycine in the N-SH2 domain that is directly involved in the intramolecular interaction between the N-SH2 and the PTP domains of the PTPN11 protein, this mutation would disrupt the N-SH2/PTP binding in the absence of a phosphopeptide, leading to an exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Consistent with these results, all previous children with NS/MPD carrying a mutated PTPN11 gene have been documented to be sporadic cases. 3,14 These findings suggest that NS/MPD is associated with mutations that might be associated with decreased fertility or have more severe consequences on fetal survival. This is consistent with the observation that mutations associated with NS/MPD have only rarely been identified in patients with familial NS cases, and that mutants detected in families transmitting NS are unlikely to be associated with NS/MPD.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Consistent with these results, all previous children with NS/MPD carrying a mutated PTPN11 gene have been documented to be sporadic cases. 3,14 These findings suggest that NS/MPD is associated with mutations that might be associated with decreased fertility or have more severe consequences on fetal survival. This is consistent with the observation that mutations associated with NS/MPD have only rarely been identified in patients with familial NS cases, and that mutants detected in families transmitting NS are unlikely to be associated with NS/MPD.…”
Section: Resultsmentioning
confidence: 95%
“…9 Infants with NS are predisposed to developing a myeloproliferative disorder (NS/MPD), which may regress without treatment or follow an aggressive clinical course similar to JMML. [10][11][12][13][14] By contrast, cases of JMML that arise in patients without NS have a poor prognosis without hematopoietic stem cell transplantation. [15][16][17][18] Recent studies show that children with JMML have improved outcomes when they are treated aggressively early in the course of disease.…”
Section: Introductionmentioning
confidence: 99%
“…For NS itself, PTPN11 mutations account for roughly 50% of cases [Musante et al, 2002;Tartaglia et al, 2002;Zenker et al, 2004]; nearly all mutations are of the missense type, although a 3-bp deletion has been observed [Yoshida et al, 2004]. PTPN11 missense mutations are also responsible for a large proportion of the patients with LEOPARD syndrome, which is allelic to NS [Digilio et al, 2002].…”
Section: Discussionmentioning
confidence: 98%
“…Notably, the cases of Doisaki et al had a mild and self-limiting clinical course. Yoshida et al also reported that a patient with Noonan syndrome developed JMML with a self-limiting course [7]. By contrast, our patient had an aggressive clinical course that was typical for isolated JMML with PTPN11 mutation.…”
Section: Discussionmentioning
confidence: 72%